Survivors of childhood and adolescent cancer a multidisciplinary approach - Schwartz, Cindy L. (Pediatric oncology, 2005)
Overview -- Algorithms of late effects by disease -- Facilitating assessment of late effects by organ system -- Central nervous system effects -- Neuroendocrine complications of cancer therapy -- Ocular complications due to cancer treatment -- Head and neck -- Adverse effects of cancer treatment of hearing -- The thyroid gland -- Cardiovascular effects of cancer therapy -- Pulmonary effects of antineoplastic therapy -- Late gastrointestinal and hepatic effects -- The ovary -- The testes -- Genitourinary -- Musculoskeletal, integument, breast -- Hematopoietic stem cell transplantation -- Second malignancies following treatment for childhood cancer -- Psychological aspects of long-term survivorship -- Legal issues -- Methodological issues in the study of survivors of childhood cancer -- Transition issues.